Herança do Potencial Hidrogeniônico e da Acidez Total Titulável em Melão - Silva, Antonia Eliziana Augusta da (2018)
The objective of this work was to study the inheritance of pH and titratable total acidity in melon. The F1, F2 and backcross generations from the AC-16 (subsp. Melo var. Acidulus) genotypes, with low pH and high titer titratable acidity, and 'Vendrantais' were evaluated in a randomized block design with three replications. subsp. melo var. reticulatus), with high pH and low total titratable acidity. It was verified that the plants of the F1 generation had a pH content and titratable total acidity with an average higher than the parents, indicating the presence of heterosis. Segregation in the F2 and backcross generations indicated that the pH value and titratable total acidity content in melon are determined by a gene with higher effect with additive effects and dominance associated with polygenes